Puppies for the Ancestors: The many roles of Shang dogs. (March 2019) - Li, Zhipeng; Campbell, Roderick
Abstract: Current anthropological approaches to animals have noted that the contemporary Western categories of human and animal are historically particular ones, and that different ontologies can and do organize the categorical and practical relationships between beings in a variety of ways. The ritual use of dogs in ancient China illustrates this point well. At Anyang (ca. 1250–1050 BCE) dogs played a number of roles in the significant doings of both kings and commoners and occupied a unique position in the Shang web of being – patterning with humans in some practices and with other domestic animals in others. The surprising discovery that Anyang mortuary ritual dogs outnumber those found in other contexts and that they are almost exclusively juvenile individuals argues for both the development of the Shang ritual economy and at the same time its basis on more than just an equation of economic expenditure with status. Finally, an epigraphic and zooarchaeological contextualization of dog sacrifice reveals that the Chinese archaeological practice of equating sacrificial deposits with whole interments reveals only the tip of the iceberg and full understanding of animal sacrifice in the Shang and other early complex societies must consider the full range of zooarchaeological deposits and cultural practices involving animals.